Gastric Hyperplasia and Increased Proliferative Responses of Lymphocytes in Mice Lacking the COOH-terminal Ankyrin Domain of NF-κB2 - Hideaki Ishikawa; Daniel R. Carrasco; Estefanı́a Claudio; Rolf-Peter Ryseck; Rodrigo Bravo (1997)
The nfkb2 gene encodes the p100 precursor which produces the p52 protein after proteolytic cleavage of its COOH-terminal domain. Although the p52 product can act as an alternative subunit of NF-kappaB, the p100 precursor is believed to function as an inhibitor of Rel/NF-kappaB activity by cytoplasmic retention of Rel/NF-kappaB complexes, like other members of the IkappaB family. However, the physiological relevance of the p100 precursor as an IkappaB molecule has not been understood. To assess the role of the precursor in vivo, we generated, by gene targeting, mice lacking p100 but still containing a functional p52 protein. Mice with a homozygous deletion of the COOH-terminal ankyrin repeats of NF-kappaB2 (p100(-/-)) had marked gastric hyperplasia, resulting in early postnatal death. p100(-/-) animals also presented histopathological alterations of hematopoietic tissues, enlarged lymph nodes, increased lymphocyte proliferation in response to several stimuli, and enhanced cytokine production in activated T cells. Dramatic induction of nuclear kappaB-binding activity composed of p52-containing complexes was found in all tissues examined and also in stimulated lymphocytes. Thus, the p100 precursor is essential for the proper regulation of p52-containing Rel/NF-kappaB complexes in various cell types and its absence cannot be efficiently compensated for by other IkappaB proteins.